High-latitude polar pattern of ionospheric electron density: Scaling features and IMF dependence. (June 2021) - Consolini, G.; Tozzi, R.; De Michelis, P.; Coco, I.; Giannattasio, F.; Pezzopane, M.; Marcucci, M.F.; Balasis, G.
Abstract: We investigated the average polar patterns of ionospheric electron density and the corresponding patterns of scaling features as a function of interplanetary magnetic field orientation. The focus is on the Northern Hemisphere using electron density data recorded on-board ESA Swarm A satellite. The first- and second-order scaling exponents have been evaluated by means of the q t h -order structure functions. We used electron density measurements over a period of 15 months from April 1, 2014 to June 30, 2015, which corresponds to the maximum of solar cycle 24 and which is characterized by an average value of the solar radio flux (F10.7) index equal to ( 140 ± 30 ) sfu. Electron density, first- and second-order scaling exponents have been mapped and discussed for four main IMF orientations provided by B y and B z components under conditions of high solar activity. Large spatial changes of the second-order scaling exponent pattern are observed with a steepening of the associated spectral exponent in correspondence with the nightside polar cap trailing edge. Intermittency, defined as the departure from linearity of the dependence of scaling exponents on moment order q, is also evaluated finding that it is generally higher near the equatorward boundary of the auroral oval than elsewhere. On the whole, the found patterns of the electron density first- and second-order scaling exponents suggest the occurrence of turbulence at the high latitudes. Highlights: The average polar patterns of ESA Swarm A electron density and of its scaling features are investigated as a function of IMF. Spatial changes of the second-order scaling exponent patterns are observed in the nightside polar cap. Intermittency is generally higher near the equatorward boundary of the auroral oval than elsewhere.